2016
DOI: 10.1161/hypertensionaha.116.07462
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Dependency of Large Artery Stiffness

Abstract: Tan et al Heart Rate Dependency of Large Artery Stiffness 237 Hemodynamic MeasurementsBrachial BP, central aortic BP, and cfPWV were determined by cuffbased pulse wave analysis (SphygmoCor XCEL, AtCor, Sydney, Australia). Brachial BP was obtained by oscillometric method with a brachial cuff positioned on the right arm, and central aortic waveform was derived from the brachial BP volume displacement waveform using a validated transfer function. 16 For measurement of cfPWV, the carotid and femoral pulse waveform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 61 publications
4
57
0
Order By: Relevance
“…The explanation for the different interaction of morning hypertension subtype with aortic stiffness is unclear. Previous studies have demonstrated a significant association of increased heart rate with PWV . Although the mechanism behind this phenomenon has yet to be firmly established, passive decrease in arterial compliance due to reduced time for elastic recoil has been suggested to be an explanation for this phenomenon .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The explanation for the different interaction of morning hypertension subtype with aortic stiffness is unclear. Previous studies have demonstrated a significant association of increased heart rate with PWV . Although the mechanism behind this phenomenon has yet to be firmly established, passive decrease in arterial compliance due to reduced time for elastic recoil has been suggested to be an explanation for this phenomenon .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated a significant association of increased heart rate with PWV. 30,31 Although the mechanism behind this phenomenon has yet to be firmly established, passive decrease in arterial compliance due to reduced time for elastic recoil has been suggested to be an explanation for this phenomenon. 31,32 We postulate that the effect of nocturnal hypertension and morning hypertension on arterial stiffening is accentuated in arteries passively stiffened by increased baseline heart rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, three constant values of elastic modulus were used for three major arterial types, and it was demonstrated that there was only a slight effect of HR on PWV. As to a positive HR dependency of PWV 6 , the frequency dependent elastic modulus E( ω ) should be considered in future research. However, realistic E( ω ) values for specific arteries are not available, even though some studies have addressed this field 3437 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently set out to quantitatively assess the physiological confounders of PWV [1], investigating the magnitude of their effect and ways to correct for them. These confounders included blood pressure [6,7,8], heart rate [9,10], and axial stretch [11]. This mini-review will concentrate on blood pressure as a confounder of PWV, and will discuss several options to deal with the confounding effect.…”
Section: Arterial Stiffnessmentioning
confidence: 99%